CONVULSIVE SYNDROME IN VICTIMS OF SEVERE TRAUMATIC BRAIN INJURY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A retrospective analysis of the results of clinical and instrumental studies and surgical treatment of victims operated on for severe traumatic brain injury in the neurosurgery department of the Multidisciplinary Clinic of the Samarkand Medical University was conducted. Epileptic seizures were registered in 140 patients (7.9%)